Konsep Berpikir Desain Untuk Meningkatkan Kapabilitas Inovasi UMKM Kabupaten Sumbawa - Fitriyani, Ika; Karmeli, Elly; Sumbawati, Novi Kadewi; Sudiharti, Nining; Rahman, Rosydah; Kamal, Afina Aurellya (Jurnal Pengabdian kepada Masyarakat Nusantara, 2025)
The importance of learning and understanding design thinking capabilities and innovation capabilities is the key to developing MSME businesses. The application of strategic concepts through design thinking and innovation capabilities is able to have entrepreneurial skills to predict better business profits in the future. The ability to think creatively and innovatively through the Bale Berdaya Sumbawa program can create collaboration for MSMEs and strengthen the local economy and improve the quality of life of the people of Sumbawa Regency. The purpose of this activity is to encourage MSME actors to develop knowledge and business success so as to create new economic opportunities. therefore, through the sharing method, discussion or question and answer online or offline which has been followed by all participants from the MSME Bale Berdaya Program, MSMEs from Car Free Day Activities and students. The benefits of this activity provide convenience and in-depth understanding to participants to always be creative, innovative, resilient and strong in facing challenges and changes in the business economy in a better future. In conclusion, this activity went smoothly and orderly and all participants were committed to advancing their products so as to produce economic welfare for their families. Therefore, in the future it is important to continue and improve it into a national seminar attended by all MSME actors along with all MSME assistants and other stakeholders on Sumbawa Island and facilitated with awards in the form of certificates for all parties involved in this program.